Expression of telomerase in atrophic endometrium in postmenopausal women - Wlaźlak, Edyta; Kobos, Józef; Bitner, Adam; Surkont, Grzegorz; Hendzel, Katarzyna; Kocięba-Gała, Barbara; Dunicz-Sokolowska, Aldona; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2007)
Telomerase is a polymerase which has the ability to elongate telomeres. Aim of the study: The aim of this study was to evaluate telomerase activity through an examination of hTERT expression in atrophic endometrium of postmenopausal women. Material and methods: 20 postmenopausal women aged 49-85 years (mean 66 yrs), who were hysterectomized because of pelvic organ prolapse or benign ovarian tumours without hormonal activity were evaluated in the study. There was found atrophic endometrium in histological examination. Telomerase expression was measured using monoclonal antibodies against protein subunit of human telomerase – hTERT. We counted cell index (percentage of cells showing telomerase activity). Results: We found telomerase expression in all examined endometrial specimens. The lower mean expression was 10%, the higher 34%. In some individual ranges we found expression between 40 and 57%. Conclusions: Atrophic endometrium in postmenopausal women shows little telomerase activity. In some cases activity is greater.